THE IMPACT OF FINANCIAL STRESS IN ADVANCED AND DEVELOPING ASIA ON INDONESIA’S STOCK MARKET RETURNS - Wira Hendri; Sahdan Saputra (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2026)
This study examines the impact of the Financial Stress Index (FSI) for Advanced Asia and Developing Asia on Indonesia’s equity returns. Monthly data from July 2003 to December 2024, comprising 258 observations, were sourced from the Asia Regional Integration Center (ARIC). The analysis utilized a Vector Autoregression (VAR) model to capture dynamic relationships among the variables. The results indicate that financial stress in Advanced Asia exerts a negative and significant short-term effect on Indonesia’s equity returns. This finding suggests a financial contagion effect, or negative spillover, from advanced Asian economies such as Japan and Australia, which are structurally integrated into the global financial system. In contrast, financial stress in Developing Asia has a positive and significant short-term impact on Indonesia’s equity returns, reflecting a reallocation spillover mechanism in which financial stress in other developing economies prompts investors to reallocate funds to Indonesia, which is perceived as more macroeconomically stable. Domestic financial stress in Indonesia demonstrates a negative but statistically insignificant effect on stock market performance. These findings underscore the need for enhanced cross-regional policy coordination and for implementing adaptive macroprudential measures to strengthen Indonesia’s capital market's resilience against regional financial risk transmission.